Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw IV Berbantuan Self Test Untuk Meningkatkan Aktivitas Dan Hasil Belajar IPA - I Gede Ariyasa (Cetta: Jurnal Ilmu Pendidikan, 2018)
This research was aimed to improve the learning activity and the students` achievement of science in the class IX-J SMPN 1 Abang in the odd semester in 2017/2018 through the implementation of the jigsaw IV cooperative learning methiode assisted self test. The hypothesis of action in this research are: (1) The implementation of jigsaw IV cooperative learning method assisted self test, can improve the achievement of students of IX-J in science in SMPN 1 Abang in the odd semester in 20017/2018. (2) The implementation of jigsaw IV cooperative learning method assisted by self test, can improve the learning activity of students of IX-J in science in SMPN 1 Abang in the odd semester in 20017/2018. This research employed classroom action research was coucted in SMPN 1 Abang. The subjects of this research were the students of IXJ in the odd semester in 2017/2018. They were 33 students with consist of 17 boys and 16 girls. This was ddesigned in three cycles of PTK Kemmis and McTaggart models. The findings shows that (1) The implementation of jigsaw IV cooperative learning method assisted by self test can improve the achiemvement of the students of IX-J SMPN 1 Abang in the odd semester in 20017/2018. (2) The implementation of jigsaw IV cooperative learning method assisted by self test can improve the leatrninga ctivity of the students of IX-J SMPN 1 Abang in the odd semester in 20017/2018.